AN ANALYSIS OF CODE SWITCHING IN FILM “THE ARCHITECTURE OF LOVE (2024)” DIRECTED BY TEDDY SORIAATMADJA - Annisa Ummi Azzahra; Dewi Rosnita Hardiany (Universitas Ngudi Waluyo, 2025)
This study aims to analyze the phenomenon of code switching in the film The Architecture of Love (2024), directed by Teddy Soeriaatmadja. Code switching, the alternation between two or more languages in communication, is commonly observed in multilingual communities and media. The film presents a unique linguistic landscape, as Indonesian and English are frequently interchanged in conversations between Indonesian characters, even without foreign interlocutors. This research used a descriptive qualitative method and Hoffman’s (1991) theory as the main framework. The study identified four types of code switching: Inter-Sentential, Intra-Sentential, Emblematic (Tag Switching), and Establishing Continuity. A total of 125 code switching were found in the film. Intra-Sentential switching was the most dominant (42 06%), followed by Inter-Sentential (33.33%), Emblematic (19.48%), and Establishing Continuity (3.97%). The study also analyzed the reasons behind these switches, with the most common being Talking about a Particular Topic (48%), Being Emphatic about Something (26%), Interjection (20%), and other sociolinguistic functions such as Expressing Group Identity, Quoting somebody else, and Clarification. The findings suggest that code switching in the film is not random but serves communicative, emotional, and identity-related purposes. It reflects the characters’ bilingual competence, emotional expression, and cultural identity, highlighting code switching as a natural and meaningful aspect of urban bilingual communication in Indonesian media.